226k views
0 votes
jorge wants to divide 3x*2−x−2 by x + 4 using synthetic division. Which answer shows the correct process?

User Popkutt
by
5.1k points

2 Answers

2 votes

Answer:

the person above me got it right but this pic is to remove any doubt :)

Explanation:

jorge wants to divide 3x*2−x−2 by x + 4 using synthetic division. Which answer shows-example-1
User Jholster
by
5.2k points
0 votes

Answer:

> Using the remainder theorem, set x + 4 to be equal to 0, i.e.

Explanation:

> Using the remainder theorem, set x + 4 to be equal to 0, i.e.

x + 4 = 0

x = - 4

=> Substitute - 4 for x in 3x² - x - 2, i.e.

3(- 4)² - (- 4) - 2

= 3 * 16 + 4 - 2

= 48 + 4 - 2

= 52 - 2

= 50 ...


-4|----3----(-1)----(-2)

-------------(-12)------52

________________

------3------(-13)----50



User Krtko
by
5.5k points